PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP PEMAHAMAN SISWA KELAS 5 DI SD NEGERI 28 PANGKALPINANG - Intan Kurnia; Diana Pramesti; Said Akhmad Maulana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was prompted by students’ limited understanding of the material. Norms in My Life in the subject of Pancasila Education. A factor that plays a role in this is the application of lecture-based teaching methods, which are still dominant. Therefore, this study applied the Think Pair Share (TPS) learning model to determine its effect on student understanding. The purpose of this research is to investigate the influence of the Think Pair Share learning model on the comprehension of fifth-grade students at SD Negeri 28 Pangkalpinang. This study uses a quantitative research design with a quasi-experimental design, using a nonequivalent control group design. Sampling was conducted using saturated sampling. The sampling technique used in this study was saturated sampling, which is a technique for determining samples when all members of the population are used as samples. The sample size was 62 students, consisting of 31 students from class 5A and 31 students from class 5B data collection was conducted via an essay test consisting of five questions, followed by data analysis involving normality and homogeneity tests, as well as hypothesis testing. The results showed that the average score of the experimental class was higher than that of the control class. The results of the study show that the average score of the experimental class is higher than that of the control class. These results are supported by the independent sample t-test, which produced a value of tcount 4.691 > greater than ttable2.000, so it can be concluded that there is an effect of the Think Pair Share (TPS) learning approach for theunderstanding of fifth-grade students at SD Negeri 28 Pangkalpinang.